A chelating diisocyanide ligand for cyclometalated Ir(iii) complexes with strong and tunable luminescence. (24th September 2015) - Monti, Filippo; Baschieri, Andrea; Matteucci, Elia; Mazzanti, Andrea; Sambri, Letizia; Barbieri, Andrea; Armaroli, Nicola
Abstract : We report the synthesis, structural characterisation and detailed photophysical description of three cationic cyclometalated iridium(iii ) complexes (2–4 ) bearing a chelating diisocyanide as the ancillary ligand (1 = 2, 2′′-diisocyano-1, 1′:3′, 1′′-terphenyl). All compounds display irreversible reduction and oxidation potentials and emit from a triplet excited state centred on the cyclometalating ligands with lifetimes of several dozen microseconds, as commonly observed for other iridium(iii ) isocyanide complexes and further confirmed by DFT calculations. Room-temperature photoluminescence can be tuned from blue to orange upon variation of the cyclometalating ligands, and the related quantum yields range from around 30% in acetonitrile solution to nearly 80% in solid-state, as for complex3 embedded in a 1% w/w poly(methyl methacrylate) matrix.